Concentration and temperature dependent selectivity of the LTCC porosification process with phosphoric acid. Issue 1 (January 2017) - Steinhäußer, Frank; Talai, Armin; Göltl, Gwen; Steiger-Thirsfeld, Andreas; Bittner, Achim; Weigel, Robert; Koelpin, Alexander; Schmid, Ulrich
Abstract: The wireless high frequency (HF) technology requires a robust, well-established and cost-effective substrate solution with a tailored permittivity. The wet-chemical porosification of low temperature co-fired ceramics provides such a substrate by locally embedding air into the surface. The present study investigates the relation of air embedment and surface alteration in detail, utilizing gravimetric methods as well as scanning electron microscopy with and without focused ion beam technology. The porosification approach could successfully be transferred from the DuPont 951, which features a high selectivity, to Heraeus CT 702 with good HF performance. By applying ring-resonator based permittivity measurements, a similar permittivity reduction by approx. 10% at a maximum frequency of 70 GHz could be confirmed. The optimum etch parameters for an LTCC allowing a further metallization are a phosphoric acid mass fraction of 50 wt%, a temperature of 100 °C at maximum and a minimum treatment time of 8 h.